1986
DOI: 10.1104/pp.81.2.478
|View full text |Cite
|
Sign up to set email alerts
|

Turgor Regulation of Sucrose Transport in Sugar Beet Taproot Tissue

Abstract: Sink tissues that store osmotically active compounds must osmoregulate to prevent excessively high turgor. The ability to regulate turgor may be related to membrane transport of solutes and thus sink strength. To study this possibility, the kinetics of sugar uptake were determined in sugar beet (Beta vulgaris L.) taproot tissue discs over a range of cell turgors. Sucrose uptake followed biphasic kinetics with a high affinity saturating component below 20 millimolar and a low affinity linear component at higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
76
1
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 14 publications
4
76
1
1
Order By: Relevance
“…At 0.2 and 0.4 M mannitol stable measurements were easier to obtain, but at 0.6 and 0.8 M mannitol, implantations became difficult again as the tissue became flaccid. (Osmotic concentration of the cell solution ranged from 0.6 to 0.75 M [17]). Attempts to measure Em during transitions from one mannitol concentration to another failed, presumably because of the movement of the tissue during changes in turgor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At 0.2 and 0.4 M mannitol stable measurements were easier to obtain, but at 0.6 and 0.8 M mannitol, implantations became difficult again as the tissue became flaccid. (Osmotic concentration of the cell solution ranged from 0.6 to 0.75 M [17]). Attempts to measure Em during transitions from one mannitol concentration to another failed, presumably because of the movement of the tissue during changes in turgor.…”
Section: Introductionmentioning
confidence: 99%
“…After incubation times of one to several hours the tissue-containing holders were inserted into Lucite chambers fitted with inlet and outlet ports for the perfusion solutions. These chambers were used in an assembly for implanting glass microelectrodes used for the measurement of Em (3, 7).Incubation of plant tissues in solutions of mannitol, or other osmotica, sometimes stimulates acidification of the bathing media (4,5,12,17) and enhances the rate of solute uptake (2,5,12,14,17). Because many solutes are cotransported with protons across plant cell membranes (3, 7, 1 1), the observed effects of the osmotica upon plant tissues can be explained by the hypothesis that high turgor inhibits the proton extrusion pump located in the plasmalemma.…”
mentioning
confidence: 99%
“…Proton extrusion across the plasma membrane is stimulated by a reduction in the external water potential mediated by any number of osmotic solutes (17,18,26,29). A substantial component of increased H+ pumping was vanadate-sensitive and it has been inferred that the plasma membrane H+-ATPase has a central function in the response to alterations in the osmotic or ionic environments (2,17,18,26).…”
mentioning
confidence: 99%
“…Finally, although Komor (10) did not pretreat his Ricinus cotyledons with high sugar levels, he did not report using an osmoticum to standardize the osmolality of each treatment. It has recently been shown that the osmolality of the uptake solution can have a pronounced effect on the uptake kinetics of some tissues ( 19).If, during the photosynthetic period, sucrose is transported across the tonoplast of mesophyll cells by a permease, then the vacuolar sucrose levels should be in near chemical potential equilibrium with the cytosol. Thus, by monitoring changes in the gross sucrose levels of the leaf, one should be able to obtain an approximate measure of the cytosolic sucrose concentration.…”
mentioning
confidence: 99%
“…Finally, although Komor (10) did not pretreat his Ricinus cotyledons with high sugar levels, he did not report using an osmoticum to standardize the osmolality of each treatment. It has recently been shown that the osmolality of the uptake solution can have a pronounced effect on the uptake kinetics of some tissues ( 19).…”
mentioning
confidence: 99%